2021
DOI: 10.3390/ph14080768
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis, Biological Evaluation, and In Silico Modeling of N-Substituted Quinoxaline-2-Carboxamides

Abstract: Despite the established treatment regimens, tuberculosis remains an alarming threat to public health according to WHO. Novel agents are needed to overcome the increasing rate of resistance and perhaps achieve eradication. As part of our long-term research on pyrazine derived compounds, we prepared a series of their ortho fused derivatives, N-phenyl- and N-benzyl quinoxaline-2-carboxamides, and evaluated their in vitro antimycobacterial activity. In vitro activity against Mycobacterium tuberculosis H37Ra (repre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 23 publications
0
4
0
Order By: Relevance
“…Further in vitro cytotoxicity on human hepatocellular carcinoma (HepG2 cell line) was evaluated which showed that compound 142 was a potential antineoplastic agent with selective cytotoxicity against hepatic (HepG2), ovarian (SK‐OV‐3), and prostate (PC‐3) cancer cell lines. Moreover, compound 142 was docked to study inhibition towards mycobacterial DprE1 where outcomes were promising [7c] …”
Section: Pharmacological Activities Of Quinoxaline‐based Compoundsmentioning
confidence: 99%
“…Further in vitro cytotoxicity on human hepatocellular carcinoma (HepG2 cell line) was evaluated which showed that compound 142 was a potential antineoplastic agent with selective cytotoxicity against hepatic (HepG2), ovarian (SK‐OV‐3), and prostate (PC‐3) cancer cell lines. Moreover, compound 142 was docked to study inhibition towards mycobacterial DprE1 where outcomes were promising [7c] …”
Section: Pharmacological Activities Of Quinoxaline‐based Compoundsmentioning
confidence: 99%
“…Quinoxaline molecules are named benzopyrazines or 1,4-benzodiazines [41][42][43]. There are four benzodiazines: quinoxaline, quinazolines, phthalazines, and cinnolines.…”
Section: Chemical Characters Of Quinoxalinesmentioning
confidence: 99%
“…In this context, the direct insertion of a nitrogen atom into the indole scaffold would represent an extremely advantageous process, as it would enable the straightforward access of N,N-heterocycles without changing the substitution pattern on the starting indole scaffold. This transformation of the indole core into such bioisosteric motifs (31,32), which are not commonly found as building blocks in medicinal chemistry libraries (33) yet are widely recognized as privileged pharmacophores in modern drug discovery (30,34), could have a transformative impact on the field of late-stage diversification, facilitating the discovery and optimization of drug candidates.…”
Section: Main Textmentioning
confidence: 99%